INCREASING STUDENTS’ VOCABULARY OF X GRADE AT SMA NEGERI 3 TOLITOLI THROUGH CROSSWORD PUZZLE - Aprilieah, Reza (Jurnal Madako Education, 2019)
This research aimed to find out the use of crossword puzzle to Increasing students’ vocabulary. The data were obtained through a pre-test and post-test. The result of this research showed that the X Grade students of SMA Negeri 3 Tolitoli had inadequate score in pre-test with the mean score 56.97. However, after receiving treatments by using Crossword puzzle Method they got high score in post-test: their mean score had increased up to 79.82. The data were analyzed by using t-test and the result showed that the t-test value 19.484 was greater than t-table value 2.037. It meant that there was a significant difference of students’ vocabulary before and after the application of it can be concluded that the use of Crossword puzzle could increase students’ vocabulary. Key words: Increasing vocabulary of crossword puzzle.